2018
DOI: 10.1063/1.5054273
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced density fluctuation assisted nucleation in polyethylene

Abstract: The nucleation process of polyethylene under quiescent and shear flow conditions are comparatively studied with all-atom molecular dynamical simulations. At both conditions, nucleation are demonstrated to be two-step processes, which, however, proceed via different intermediate orders. Quiescent nucleation is assisted by local structure order coupling conformational and local rotational symmetric orderings, while flow-induced nucleation is promoted by density fluctuation, which is a coupling effect of conforma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 63 publications
4
47
0
Order By: Relevance
“…The crystal cluster shown in Figure 1 corresponds to 600 carbon atoms, the approximate critical nucleus size for the conditions and molecular model used in this study (see [38]). The varying stem lengths in Figure 1 along with similar simulation snapshots from previous studies [17,19,20,[27][28][29][30][31][32][33][34] highlight that structural non-uniformity (heterogeneity) is present at the early stages of crystallization in a monodisperse polymer melt. This study contributes a detailed quantitative characterization and discussion of this structural heterogeneity.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The crystal cluster shown in Figure 1 corresponds to 600 carbon atoms, the approximate critical nucleus size for the conditions and molecular model used in this study (see [38]). The varying stem lengths in Figure 1 along with similar simulation snapshots from previous studies [17,19,20,[27][28][29][30][31][32][33][34] highlight that structural non-uniformity (heterogeneity) is present at the early stages of crystallization in a monodisperse polymer melt. This study contributes a detailed quantitative characterization and discussion of this structural heterogeneity.…”
Section: Resultssupporting
confidence: 72%
“…Based on the visual inspection of snapshots from nucleation simulations, Meyer and Müller-Plathe [26] noted in passing that nuclei could be composed of stems of varying length and contain a variable number of stems. Similarly, images of polymer crystal nuclei from previous work [15,17,19,20,23,[27][28][29][30][31][32][33][34][35][36] exhibit stem length variability, and sometimes quite pronounced variability, though these studies did not directly explore nor quantify the stem length distributions of nuclei. More recently, Hagita et al [37] demonstrated that stem length probability distributions broaden as linear and ring polyethylene melts crystallize, though multiple nuclei of differing size formed in their systems, obfuscating the structural details of individual nuclei.…”
Section: Introductionmentioning
confidence: 96%
“…Our insights align well with results from previous computational studies 35,50,51,55,58,59 on polymer and alkane crystallization. Zhang and Larson 35 recently demonstrated that quenching polyethylene melts below their isotropic-nematic transition temperature (T IN ) results in rapid crystal nucleation on timescales <100 ns, which is much shorter than the microsecond induction times associated with this study's simulations (see Fig.…”
Section: Resultssupporting
confidence: 89%
“…They also observed nascent hexagonal structuring temporally preceding changes in the Voronio volume (local density) of carbon atoms. Moreover, subsequent work by Tang et al 50 on shear-induced crystallization suggests that chain alignment and densification precede crystallization under shear conditions. For reference, Tang et al assigned particles as crystalline using a metric based on spherical harmonics and similar in spirit to q 6 q * 6 , so their observations could correspond to a scenario where the q 6 q * 6 and ρ curves in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some research groups have reported that shear temperatures above the equilibrium melting temperature change the features of FIPs, further affecting the crystallization morphology and crystallization rate of polymers in the melt. [20][21][22][23] In this work, we studied the effects of FIPs on the crystallization of P3HT in solution, and the equilibrium dissolution temperature T 0 d needs to be evaluated to determine a suitable shear temperature. The Hoffman-Weeks method was used to measure the T 0 d of P3HT toluene solution.…”
Section: Effect Of the Shear Temperature On The Solution Crystallization Kineticsmentioning
confidence: 99%